Proceedings of the 1st International Conference on Social, Applied Science and Technology in Home Economics (ICONHOMECS 2017) 2018
DOI: 10.2991/iconhomecs-17.2018.12
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Motivation and Competence Factor on Lecturers' Performance in Universitas Negeri Surabaya

Abstract: This research aims to analyze the influence of competence and motivation on lecturers performance is in the home economics department of Universitas Negeri Surabaya. The data obtained through questionnaire and analyzed for multiple regression through Statistical Social Science Program (SPSS). The results show that the competence and motivation variables partially have a significant effect on performance. This research supports the efforts to improve lecturers' performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…, 2018). In addition, Handajani et al. (2017) found that motivation and the competencies of the lecturers have a positive effect on their performance.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2018). In addition, Handajani et al. (2017) found that motivation and the competencies of the lecturers have a positive effect on their performance.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Therefore, motivation and satisfaction are the strong intrinsic that enhance commitment, loyalty and performance of the employees (Theresia et al, 2018). In addition, Handajani et al (2017) found that motivation and the competencies of the lecturers have a positive effect on their performance. Schulz and Steyn (2003) found that older and experienced teachers are motivated by a good working environment at the workplace.…”
Section: Job Motivationmentioning
confidence: 99%
“…For a rapid development, the trend of delivering advanced education should not stop and the importance of educators should be realized for teaching advanced information to ensure the development of students (Cho & Perry, 2012). The main objective of specialized development of teachers is to ensure the recovery of accomplishments made by students with their knowledge (Handajani et al, 2017). It is suggested that specialized uplifting of teachers is required with the help of information development, capability, and improved knowledge for better classroom performance and enhanced quality of classroom practices which will increase the achievements and knowledge of students.…”
Section: Educational Research and Innovation (Eri)mentioning
confidence: 99%